PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN KEPUASAN KERJA TERHADAP KINERJA KARYAWAN PT SEMEN PADANG DEPARTEMENT SUMBER DAYA MANUSIA - Doni Marlius; Raveena Azhari Melaguci (Jurnal Bina Bangsa Ekonomika, 2024)
This research aims to determine the influence of leadership and job satisfaction on employee performance at PT Semen Padang Human Resources Department. There were 38 respondents in this study using the Total Sampling technique. The data analysis used is multiple linear regression. The test results show that transformational leadership has a positive and significant influence on employee performance and job satisfaction also has a positive and significant influence on employee performance